-9(y+1)=3(y-3)-36

Simple and best practice solution for -9(y+1)=3(y-3)-36 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -9(y+1)=3(y-3)-36 equation:


Simplifying
-9(y + 1) = 3(y + -3) + -36

Reorder the terms:
-9(1 + y) = 3(y + -3) + -36
(1 * -9 + y * -9) = 3(y + -3) + -36
(-9 + -9y) = 3(y + -3) + -36

Reorder the terms:
-9 + -9y = 3(-3 + y) + -36
-9 + -9y = (-3 * 3 + y * 3) + -36
-9 + -9y = (-9 + 3y) + -36

Reorder the terms:
-9 + -9y = -9 + -36 + 3y

Combine like terms: -9 + -36 = -45
-9 + -9y = -45 + 3y

Solving
-9 + -9y = -45 + 3y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-3y' to each side of the equation.
-9 + -9y + -3y = -45 + 3y + -3y

Combine like terms: -9y + -3y = -12y
-9 + -12y = -45 + 3y + -3y

Combine like terms: 3y + -3y = 0
-9 + -12y = -45 + 0
-9 + -12y = -45

Add '9' to each side of the equation.
-9 + 9 + -12y = -45 + 9

Combine like terms: -9 + 9 = 0
0 + -12y = -45 + 9
-12y = -45 + 9

Combine like terms: -45 + 9 = -36
-12y = -36

Divide each side by '-12'.
y = 3

Simplifying
y = 3

See similar equations:

| pr+qs=4 | | 0.1888888888888888888888888888888888= | | 37.68=(2)(3.14)(x+1) | | -5(2x-3)-5x=120 | | 8-3(x+4)=2x+1 | | -3(4-7x)=93 | | 7n+12=.50(14n+24) | | 90-x=1/5(180-x) | | 2V+7=5 | | 2x+7-7x=-33 | | 171/90 | | 1-9n^2=-124 | | x+9+x=79 | | 10x-75=-25x+275 | | x^2+(3k+1)x+8=0 | | ln(ln*x)=-2.2 | | 3+8x=9+6x | | 0.8/40 | | 3+8x=96x | | 2(-4b)+6b=-10 | | 2ln(9-7p)+1=7 | | .12y+.07(y+3000)=1350 | | X/3=7^2-2 | | 28+7m=3m | | -49m-13=99 | | -2y+3y=-3 | | 2(4-s)=-12 | | 0=10t^2-120t | | 15ln(4x-3)=48 | | y-1=-2(x+6) | | 2x+3.4=5.6 | | 12+5m=32 |

Equations solver categories